TEEN PREGNANCY: OBSTETRIC COMPLICATIONS - Tay, Flor (2015)
Objective: To know the main obstetric complications of pregnancy in adolescents (11- 19 years) during 1992-1993. Design: Retrospective study at Hospital III, Sullana- Perú. We reviewed 947 clinical historis. We compared this group with another (n = 947) age 20 to 34 years (control group). The statistic analysis used frequencies, rates, standard desviation (SD) and the x2 test. Results: The incidence of pregnancy in adolescents was 12,9%, average age 17,7 years; 62,8% had 18 to 19 years, 54% cohabited with the infants lather and 7,2% were singles; 75,8% were primiparas. Compared with control group the adolescent group had higher frequency of cesarean section (14,9% vs 6,5%). We found a relation between pregnancy in adolescents and perineal laceration, cephalopelvic disproportion, acute fetal distress, abortion, urinary tract infection and anemia. Conclusion: Pregnancy in adolescents has a high risk for the mother and her product. We must encourage an integral care of adolescents to avoid unwished pregnancies and associated complications.